Papillary Thyroid Cancer-Promoting Activities of Combined Oral Contraceptive Components: - Rajabi, Sadegh; Nikzamir, Abdolrahim; Hedayati, Mehdi (Galen Medical Journal, 2020)
Background: Thyroid cancer is more common in women at reproductive age, suggesting the relationship between its high-incidence and therapeutic use of hormonal medications, such as oral contraceptives (OCPs). The aim of this study was to identify the effect of low-dose combined OCP (LD-COC) on proliferation, apoptosis, and migration of human papillary thyroid cancer (PTC) BCPAP cell line. Materials and Methods: BCPAP cells were cultured and treated with the combination of 90nM levonorgestrel (LNG) and 20nM ethinylestradiol (EE) for 48 hours. Afterward, using 3-(4, 5-dimethylthiazol-2-yl) -2, 5-diphenyltetrazolium bromide (MTT) assay, the proliferation of the cells was measured. Apoptosis was determined by using a Caspase-3 ELISA kit. Migratory properties of combined LNG and EE were studied through wound scratch assay. The expression levels of pro-apoptotic factor BAX, anti-apoptotic factor Bcl2, and proliferation marker Ki67 were analyzed by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) and western blotting. Results: Upon treatment with the combination of LNG and EE, proliferation and migration of BCPAP cells were significantly enhanced. However, LNG and EE remarkably inhibited apoptosis of these cells. Furthermore, treating PTC cells with combined LNG and EE caused a marked increase in the expression of Bcl2 and Ki67 and a considerable decrease in BAX levels (P˂ 0.05). Conclusion: Our data linked the use of COCs and the progression and aggressiveness of PTC, suggesting the role of these hormonal compounds as promoting factors for PTC tumors. Despite these observations, further investigations will be required to fully establish the pathogenic impact of these medications on PTC. [GMJ.2020;9:e1648]